The implementation of International Criminal Law obligations - particularly international crimes within domestic systems: An overview of processes in Colombia, Peru and Venezuela - Ospina, Juan Carlos (2021)
Latin America has not been unaffected by situations of armed conflict or other situations of violence. These situations require analysis from both theoretical and practical approaches. A key component of these analysis has been - and continues to be - the need to guarantee the compatibility of national legal systems with International Criminal Law, with the aim of fighting against impunity and to prevent the commission of international crimes. This translates into the need to carry out a comprehensive implementation of obligations arising from relevant treaties in this area ratified by States. This factor could guarantee that countries in the region have adequate legal tools to make a correct legal assessment of armed conflicts or situations of violence which may amount to international crimes and crimes related to the use of force by State agents; in order to apply the relevant legal framework according to the characteristics of a specific context and time; and to prosecute criminal conducts using the criminal offenses that best respond to the nature of the events and the context in which they took place. In this sense, this paper contains an analysis of the status of the national implementation in Colombia, Peru and Venezuela of international obligations regarding international crimes as well as, where relevant, crimes related to the use of force by State agents. Thus, the authors aim at identifying legislative successes and gaps, regulatory practices for implementation, as well as the contributions of case-law that have complemented current legal frameworks.